The Public Relations Strategy of The West Java Provincial Education Office in Forming A Positive Image of Institutions: Case Study on Public Relations of West Java Province Education Office - Dinar Binugraheni; Oji Kurniadi (UNISBA Press, 2022)
Abstract. in supporting the success of a predetermined plan, public relations of an organization or government agency requires the right strategy in order to achieve the intended target. In this study, we will discuss the